Seroepidemiology of hepatitis A, hepatitis B and varicella virus in people living with HIV in Ireland. Issue 6 (November 2017) - Sadlier, Corinna; O'Rourke, Anna; Carr, Alison; Bergin, Colm
Abstract: Epidemiological studies investigating seroprevalence of vaccine preventable infections at both individual and population level are important in guiding screening and vaccination practices. Data on seroprevalence of common vaccine preventable infections in HIV-infected individuals is lacking. We carried out a retrospective cohort study to investigate serological immunity and factors associated with immunity to hepatitis A virus (HAV), hepatitis B virus (HBV) and varicalla virus (VZV) in a cohort of HIV-infected individuals attending a large ambulatory HIV specialist centre in Ireland. Basic demographic data including risk of acquisition of HIV and region of origin was recorded. Between-group prevalence was compared using the Chi2 test and Wilkoxin signed rank test. Univariate variables with p < 0.2 were entered into a multivariate logistic regression model. Of 1287 HIV-infected individuals included in this study (median [SD] age 39 [10] years, 68% male, 46% Irish), 75% were hepatitis A IgG positive, 94% were VZV IgG positive, 3% were HBV surface antigen (sAg) positive while 29% were HBV core antibody (cAb) positive. This study identifies a significant proportion of HIV infected who were susceptible to common vaccine preventable infections. These results highlight the importance of proactive screening and immunization of HIV-infected individuals to ensure optimal protect ionagainst vaccine preventable diseases in this at risk patient group.